The effect of Intelligence Quotient (IQ) and Adversity Quotient (AQ) on soft skills competency development in maritime vocational education - Ardhiana Puspitacandri; Saliman Saliman; Yoyok Soesatyo (Jurnal Pendidikan Vokasi, 2024)
This research aims to determine the effect of intelligence on soft skill competence and to analyze models predicting improvements in soft skill competence based on intelligence in maritime vocational colleges under the Ministry of Transportation, which is responsible for producing seafarers in Indonesia. This study employs a quantitative and inferential approach to test the hypothesis. Data were collected from 217 prospective graduates at the Politeknik Pelayaran Surabaya, Indonesia. The sampling technique used is stratified cluster random sampling, selecting samples from three majors: Nautical, Engineering, and Electrical. The instruments used in this research include standardized tests and a questionnaire, both of which have been tested for validity and reliability. Data analysis was conducted using Partial Least Squares (PLS) with Smart PLS software to examine the structural relationships among variables and produce a predictive model of soft skill competence based on intellectual intelligence (IQ) and Adversity Quotient (AQ). The results of this study indicate a significant and positive direct influence of IQ on soft skill competence by 50% and an indirect influence of IQ on soft skill competence through AQ by 6.8%. The analysis further reveals a positive and significant influence of IQ on AQ by 21.4% and a direct positive influence of AQ on soft skill competence by 31.8%. The structural analysis of the model using PLS demonstrates that IQ and AQ together influence soft skill competence with an overall predictive power of 44.9%. This research contributes to understanding the relationship between intelligence and soft skills development, which can serve as a foundation for formulating maritime vocational education policies. The findings highlight the importance of integrating both cognitive intelligence and resilience-building strategies into maritime education curricula to enhance the preparedness and employability of future seafarers.